Assessing the application and limitations of a standardised overheating risk-assessment methodology in a real-world context. (15th August 2020) - Mourkos, Konstantinos; McLeod, Robert S.; Hopfe, Christina J.; Goodier, Chris; Swainson, Michael
Abstract: Prolonged overheating has severe consequences for the future habitability of buildings. Building Performance Simulation (BPS) is increasingly used to identify the propensity of buildings to overheat, however the reliability of this approach has been repeatedly questioned. A new overheating risk-assessment methodology, Technical Memorandum (TM)59 was developed by the Chartered Institution of Building Services Engineers (CIBSE), to address this problem by providing a consistent framework for the evaluation of overheating risks in new homes. To date, little empirical research has been carried out to validate this approach in comparison to real buildings. This study aims to bridge the gap between theory and praxis by investigating the potential challenges, limitations, and implications of implementing this standardised methodology. This was achieved by comparing BPS simulations, based on the application of TM59, with empirically measured data from three recently constructed energy-efficient flats located in London. The flats were monitored during the late autumn in order to assess their propensity to chronic year-round overheating, outside of the summer season. Distinct user scenarios, based on different modes of ventilation and window/shading operation, were analysed in relation to the CIBSE TM59 overheating thresholds. The results showed that the TM59 criteria were extremely difficult to satisfy. Under a mechanical ventilation assessment mode (with windows closed) 30–67% of the total occupied hours exceeded the overheating thresholds. This analysis has highlighted the need to further improve overheating methodologies, by considering the assessment of risks in discrete temporal bands as well as incorporating methods to assess mixed-mode purge-ventilation strategies. Highlights: Discrepancies between simulated and monitored overheating data were significant. Simulations over-predicted the amplitude of the diurnal temperature fluctuations. TM59 overheating criteria are stringent and proved difficult to satisfy. Using mechanical ventilation 30–67% of occupied hours exceeded overheating thresholds. Revised temporal banding of zonal thresholds improves the utility of risk assessments.